2020
DOI: 10.1021/acs.jpca.0c04588
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Theoretical Study on the Stability of CL-20-Based Host–Guest Energetic Materials

Abstract: CL-20-based host−guest complexes are promising energetic materials, which are prepared by embedding small molecules into the crystal lattice cavity of anhydrous CL-20. The structure, interaction, stability, and detonation performance of a series of host−guest complexes were investigated by the combination method of density functional theory and experiment. Both the crystal structure of α-CL-20/H 2 O and α-CL-20/N 2 O revealed by powder X-ray diffraction and the thermal stability order of α-CL-20/N 2 O, α-CL-20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 25 publications
1
17
0
Order By: Relevance
“…These void spaces can also be exploited to synthesize CL-20 solvates with superior detonation properties, where the crystal water is replaced by hydrogen peroxide or nitrous oxide [18,23]. Recently, computational studies on the effects of small guest molecules embedded in the crystal lattice of anhydrous α CL-20 have been conducted, and structural, electronic, and detonation properties of the guest-host crystals were discussed [24][25].…”
Section: Introductionmentioning
confidence: 99%
“…These void spaces can also be exploited to synthesize CL-20 solvates with superior detonation properties, where the crystal water is replaced by hydrogen peroxide or nitrous oxide [18,23]. Recently, computational studies on the effects of small guest molecules embedded in the crystal lattice of anhydrous α CL-20 have been conducted, and structural, electronic, and detonation properties of the guest-host crystals were discussed [24][25].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the computationally-obtained UV spectrum of a CL-20 photolysis product was matched with the experimental spectrum [25]. Recently, computational studies have been conducted on the effects of small guest molecules embedded in the crystal lattice of anhydrous α CL-20 [26][27], discussing structural, electronic, and detonation properties of the guest-host crystals.…”
Section: Introductionmentioning
confidence: 85%
“…We used the generalized gradient approximation with the Perdew-Burke-Ernzerhof (PBE) functional [38] and projector-augmented wave potentials [39]. The PBE functional has recently been applied to describe the effects of small guest molecules embedded in the crystal lattice of anhydrous α CL-20 [26][27]. We carried out non-spin polarized calculations, except for NO 2 and CL-20 containing NO 2 , in which cases the spin polarized variant was utilized.…”
Section: Methodsmentioning
confidence: 99%
“…There are signi cant differences in the energy densities, detonation performance, and other aspects of host-guest systems obtained by adding different guest molecules 5 . For instance, Xu et al 6 compared the calculated detonation velocity/pressure values of HNIW/N2O and HNIW/CO2, and the results all showed that the detonation velocity/pressure of HNIW/N2O was superior to that of HNIW/CO2.…”
Section: Introductionmentioning
confidence: 99%